The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1063/1.122910
|View full text |Cite
|
Sign up to set email alerts
|

Atomic structure and electronic properties of single-wall carbon nanotubes probed by scanning tunneling microscope at room temperature

Abstract: A detailed three-dimensional structural analysis of single-walled carbon nanotubes was carried out using a scanning tunneling microscope (STM) operated at room temperature in ambient conditions. On a microscopic scale, the images show tubes condensed in ropes as well as tubes which are separated from each other. For a single-wall nanotube rope, the outer portion is composed of highly oriented nanotubes with nearly uniform diameter and chirality. On separated nanotubes, atomically resolved images show variable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(37 citation statements)
references
References 7 publications
3
33
1
Order By: Relevance
“…Topographic imaging can be combined with tunneling spectroscopy measurements. [5][6][7][8] This is a powerful technique since the predicted relation between atomic and electronic structure can be tested. STM measurements indeed confirmed that nanotubes can be either semiconducting or metallic, depending on the chirality and diameter.…”
Section: 6mentioning
confidence: 99%
“…Topographic imaging can be combined with tunneling spectroscopy measurements. [5][6][7][8] This is a powerful technique since the predicted relation between atomic and electronic structure can be tested. STM measurements indeed confirmed that nanotubes can be either semiconducting or metallic, depending on the chirality and diameter.…”
Section: 6mentioning
confidence: 99%
“…High quality and well-aligned carbon nanotubes are essential for the applications in the field of nanoelectronics and many of these applications are dependent upon the chirality and diameter of CNTs [7]. The nanotubes can be either metallic or semiconducting depending upon their diameter and chirality.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11] These predictions have been confirmed by Raman experiments 12) and direct measurements of local density of states by scanning tunneling spectroscopy. [13][14][15] In this paper we shall investigate effects of potential scattering in metallic nanotubes in the case of the presence of several current carrying channels.…”
Section: Introductionmentioning
confidence: 99%